DISSERTAÇÕES E TESES: (1993 à abril de 1994) - Silvia Passos, Carmen; Augusto, Mário; Regina Lemes , Mara; Carlos, João; Maria dos Santos, Arlete; Wanda Dicz, Rosa; Regina Leoni Silva Lima de Queiroz, Kátia; Pedroso, Sandra; Catarina, Erly; Magali Stelato Rocha, Maria; et al. (Revista de Ciências Médicas, 1995)
DISSERTAÇÕES E TESES (1993 À ABRIL DE 1994)